Analysis of localisation of megakaryocytes in the bone marrow of the rat - possible relationship with innervations - Piątek, Małgorzata; Polaniak, Renata; Tabarowski, Zbigniew; Staśkiewicz, Wiktoria; Kiciak, Agata; Grajek, Mateusz (Journal of Education, Health and Sport, 2022)
Within the bone marrow, megakaryocytes thrive in an environment rich in numerous growth factors that influences their development, maturation, and may play a role in signaling the start of platelet production. Up to now, experiments concerning localisation of various populations of cells in rat bone marrow showed their certain relationship to the blood vessels. There are strikingly few reliable sources of information available in the literature that confirm the relationship between the localisation of these cells in connection to nerve fibers. Therefore the purpose of the present study was to examine if megakaryocytes are located in a defined relation to sensory and sympathetic nerve fibers. The study used immature 6 weeks rats of the Wistar breed of both sexes. The animals were kept under constant lighting conditions (12 hours light-dark cycle) and temperature, and had unrestricted access to water and food (standard laboratory rodent feed).Double immunostaining method was applied with usage of secondary antibodies conjugated with fluorochromes (Cy3 and DTAF) to identify cells. The antibody against CD42d was used to immunolocalise megakaryocytes, while in order to identify the distribution of nerves, antibodies anti-NPY (for detection sympathetic nerve fibers) and anti-PGP 9.5 (sensory nerve fibers) were applied. These findings showed the presence of megakaryocyte and megakaryoblastic cells which were distributed with a close relationship to the blood vessels but some of them were located in parenchyma. It was shown that NPY-positive and PGP 9.5-positive cells were present in the vicinity of blood cells. Furthermore, some megakaryocytes were located near PGP 9.5-labelled cells. The relationship between sympathetic nerve fibers containing neuropeptide Y and megakaryocytes was also detected.